OVERVIEW OF AGRICULTURAL HOLDINGS IN ROMANIA AND THE EUROPEAN UNION - Gabriela-Dalila STOICA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study aims to complement previous studies and create an overview of the subject of agricultural holdings both at the Romanian and European level. According to the statistical data and using a quantitative and qualitative research method, it was found that more than 30 years after the restoration of land ownership, a percentage of approximately 96% of the holdings in Romania are smaller than 10 hectares, while over 70% of them are represented by farms up to 2 hectares. Therefore there huge differences and discrepancies between Romania and other EU countries in terms of agricultural holdings. The results obtained confirm that small-sized farms are found in countries such as Romania, Malta, Cyprus, Greece and Portugal, while medium-sized holdings are found especially in countries such as Poland, Spain and Italy, the rest of the holdings, those between 50 and over 100 hectares, they are mostly found in Luxembourg, Finland, the Netherlands and even Germany and France.